Observation of magnetic resonance imaging of pelvis and post operative findings in cases of rectal carcinoma - Tanjum, Tasmia; Islam, M. Sarower; Saha, Papri; Imran, Ahmed; Bhowmik, Ratan Chandra; Sharmin, S. M. Ferdous Jahan Begum; Rahman, Mohammad Sabidur; Hossain, M. Altaf (International Surgery Journal, 2024)
Background: Colorectal carcinoma, the most common malignancy within the gastrointestinal tract, ranks second in cancer-related fatalities across Western Europe and the United States, with approximately one quarter of cases located in the rectum. The purpose of this study was to evaluate magnetic resonance imaging (MRI) findings and analyze postoperative outcomes in the pelvic region of patients diagnosed with rectal carcinoma. The aim of this study was to observe MRI findings and postoperative outcomes in the pelvic region of patients diagnosed with rectal carcinoma. Methods: This cross-sectional study at Dhaka medical college hospital spanned 24 months from July 2021 to June 2023, involving 90 patients with provisional rectal carcinoma diagnoses. Patients underwent MRI using the Hitachi Echelon 1.5 T MR system™ for assessment of lesion site, tumor characteristics, lymph node involvement, and local organ status. Histopathological evaluation followed the WHO grading system and AJCC TNM classification, 8th edition. Statistical analysis was conducted using SPSS version 23.0 with significance set at p<0.05. Results: In 90 patients with rectal carcinoma, common comorbidities included diabetes (30%) and hypertension (23.3%). MRI showed mid-rectal tumors (47.8%), mainly hypointense on T1WI (81.1%) and hyperintense on T2WI (96.7%). Tumor staging identified T2 in 36.7% and lymph node involvement (N0) in 50.0%. About 38.9% patients were found in T2 staging and 53.3% patients in N0 group identified by histopathology. Conclusions: MRI findings in rectal carcinoma correlate well with histopathology, underscoring MRI's clinical utility and suggesting potential for enhancing diagnostic accuracy in future research.